الدعم المنظمي واثرة في تعزيز السيادة الاستراتيجية: Organizational support and its impact on enhancing strategic sovereignty - an analytical study of the opinions of senior leadership in the General Company for Southern Cement Industry - اكرم محسن مهدي الياسري; فيصل علوان الطائي; علي كاظم حسين الشريفي (Iraqi Journal for Administrative Sciences, 2024)
The study focused on the relationship and impact between organizational support and strategic supremacy. The study aims at determining the dimensions of organizational support and its impact on enhancing strategic supremacy. The research was based on a set of references and scientific sources that dealt with this subject. An objective sample was chosen consisting of (116) leaders in the General Company for the Southern Cement Industry. The aspects of the study focused on highlighting the role of the dimensions of the organizational support to enhance the strategic supremacy. The questionnaire was used as a means of collecting data and information. It was analyzed using a set of statistical methods( Simple, multiple regression coefficient) and the results were extracted through the statistical program (spss vs.23). The most important conclusions that after the incentives did not receive sufficient attention by the sample members under study it helps to achieve the smoothness of work and raise the morale of the workers in order to contribute to strengthen the capabilities of the company under study towards this phenomenon of competition, and the most important recommendations to encourage the behavior of citizenship organizational, Commitment to career and job satisfaction creates a kind of competition in voluntary work around to make additional efforts to increase productivity efficiency thereby enhancing the strategic supremacy of the company under study.